Religious terrorism, forced migration, and women's empowerment: Evidence from the Boko Haram insurgency - Paola Elice; Fernanda Martínez Flores; Arndt R. Reichert (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
We examine the link between violent attacks of the Islamic extremist group Boko Haram, forced migration, and the empowerment of women in host communities. We find positive effects of distant attacks on the economic well-being of women, their use of modern contraceptive methods, and rejection of traditional gender views. At the same time, however, the findings show an increase in the risk that women experience domestic violence. We then examine forced displacement as a channel and its importance relative to other possible channels for the spatial effect dispersion. The results are different for Fulani pastoralist-farmer clashes over natural resources.
Keywords: D74; J22; O12; O15; R23; 330; Boko Haram; Fulani; conflict; forced displacement; female labor force participation; employment; fertility; social norms; gender norms